Perioperative urinary heat shock protein 72 as an early marker of acute kidney injury in dogs. (January 2020) - Kavkovsky, Anastasiya; Avital, Yochai; Aroch, Itamar; Segev, Gilad; Shipov, Anna
Abstract: Objective: Acute kidney injury (AKI) may be a complication in dogs undergoing surgery. Urinary heat shock protein 72 (uHSP72) is a sensitive biomarker of canine AKI. To assess the occurrence of perioperative AKI, based on uHSP72 compared with serum creatinine (sCr), and whether its occurrence is associated with the American Society of Anesthesiology physical status (ASA status). Study design: Clinical prospective study. Animals: A total of 80 client-owned and shelter dogs. Methods: Dogs scheduled for elective or emergency surgery were assigned ASA status (ASA I–IV). Preoperative and 24 hour postoperative serum and urine samples were collected. sCr, uHSP72 and urinary creatinine (uCr) were measured. Results: Postoperative uHSP72/uCr concentration [median (range)] of all dogs undergoing surgery [2.40 (0.14–252) ng mg −1 ] was significantly increased compared with preoperative uHSP72/uCr [1.30 (0.11–142) ng mg −1 ] concentration ( p < 0.001). Conversely, postoperative sCr concentration of all dogs [0.88 (0.3–1.6) mg dL −1 ] significantly decreased compared with preoperative sCr concentration [0.8 (0.2–5.0) mg dL −1 ; p = 0.001]. Median uHSP72/uCr concentration differed both preoperatively ( p = 0.007) and postoperatively ( p = 0.019) among the ASA status groups. Increased uHSP/uCr was measured in 20 dogs preoperatively and 33 dogs postoperatively, whereas only five dogs fulfilled the criteria of AKI based on sCr. Conclusions: The occurrence of increased uHSP72/uCr perioperatively suggests that the proportion of dogs with AKI is considerably higher than perceived. Clinical relevance: Dogs undergoing surgery should be closely monitored for AKI before and after anesthesia, using currently available markers (e.g., sCr) and more sensitive markers.